Interactions between below‐ground traits and rhizosheath fungal and bacterial communities for phosphorus acquisition - Honvault, Nicolas; Houben, David; Firmin, Stéphane; Meglouli, Hacène; Laruelle, Frédéric; Fontaine, Joël; Lounès‐Hadj Sahraoui, Anissa; Coutu, Arnaud; Lambers, Hans; Faucon, Michel‐Pierre (Functional ecology, 2021)
Plant–soil–microbe interactions play a central role in plant nutrient acquisition and thus ecosystem functioning and nutrient availability in agroecosystems. Adjustments in root morphology, root exudation and associations with micro‐organisms such as arbuscular mycorrhizal fungi are common for phosphorus acquisition. Yet how plant below‐ground functional traits interact with microbial communities for P acquisition remains largely unknown, limiting our understanding of phosphorus availability in agroecosystems. Interactions between below‐ground functional traits and rhizosheath soil microbial communities for P acquisition were investigated across eight herbaceous species with contrasting root traits. Root morphological and physiological traits involved in P acquisition were quantified simultaneously with PLFA (phospholipid fatty acid) and NLFA (neutral lipid fatty acid) microbial bioindicators. Multiple correlations were observed between root morphology, root exudates and rhizosheath fungal and bacterial communities. Root exudates and in particular release of malate and malonate were strongly linked with indicators of Gram‐negative bacteria, which were correlated with changes in rhizosheath soil P concentration and plant P content. Our results suggest that root exudation of carboxylates may play an important role in plant–soil–microbe interactions for P acquisition, underlining their likely role in shaping microbial communities. Incorporating these interactions in biogeochemical models would lead to better predicting power and understanding of P cycling and ecosystem functioning. A free Plain Language Summary can be found within the Supporting Information of this article. Résumé Les interactions plante‐sol‐microbe jouent un rôle central dans l'acquisition d’éléments nutritifs par les plantes et par conséquent dans le fonctionnement des écosystèmes et la disponibilité des nutriments dans les agroécosystèmes. L’acquisition du phosphore nécessite souvent des ajustements entre morphologie et exsudations racinaires ainsi que l'association des racines avec les micro‐organismes du sol tels que les champignons mycorhiziens arbusculaires. Les mécanismes par lesquels les traits fonctionnels des plantes interagissent avec les communautés microbiennes pour l'acquisition de P restent pourtant largement méconnus, limitant ainsi notre compréhension de la disponibilité du phosphore dans les agroécosystèmes. Les interactions entre traits fonctionnels souterrains et communautés microbiennes du sol rhizosphérique pour l'acquisition de P ont été étudiées au sein de huit espèces herbacées aux traits racinaires contrastés. De multiples traits morphologiques et physiologiques racinaires impliqués dans l'acquisition de P ont été quantifiés simultanément avec plusieurs bioindicateurs microbiens (PLFA et NLFA). De nombreuses corrélations ont été observées entre la morphologie racinaire, les exsudats racinaires et les communautés fongiques et bactériennes du sol rhizosphérique. Les exsudats racinaires, en particulier la libération d'acide malique et malonique, étaient fortement liés aux indicateurs de bactéries Gram‐négatives, eux‐mêmes corrélés aux changements de la concentration en P du sol rhizosphérique et à la teneur en P des plantes. Nos résultats suggèrent que l'exsudation racinaire des carboxylates joue un rôle important dans les interactions plante‐sol‐microbe pour l'acquisition de P, soulignant leur rôle probable dans la formation des communautés microbiennes. L'intégration de ces interactions dans les modèles biogéochimiques conduirait à une meilleure précision ainsi qu’à une meilleure compréhension du cycle du P et du fonctionnement des écosystèmes. A free Plain Language Summary can be found within the Supporting Information of this article.